Pengaruh Variasi Penambahan Limbah Plastik Terhadap Kekuatan Tekan Batako Dalam Upaya Pemanfaatan Limbah - Kusdiyono Kusdiyono; Supriyadi Supriyadi; Mochammad Tri Rochadi; Herry Ludiro Wahyono (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2018)
At this time, plastic is a material that is needed by the public at large and the impactis also extraordinary after the plastic is used in daily life which can cause seriousproblems if the management is not done properly. The problem of plastic waste doesnot only occur in the city of Semarang, but also in other cities, so the Ministry ofEnvironment and Forestry has implemented a pay-for-use plastic bag program inthe short term. But this is only to deal with problems in the short term. In the longterm, it will not solve the problem of "plastic waste", because the policy actuallyencourages people to buy plastic that is of course will add a new burden to thepeople to buy it. The results showed that the compressive strength of a hollowconcrete brick (brick) with a model / type BN d.d. B1,0 there is a decrease in theaverage compressive strength. The highest at the addition of 0.10% withcompressive strength on average reached 35.21 kg / cm², in general the decreaseoccurred in the addition of plastic each different from 0.10% to 1.0% of the weightof sand with the lowest compressive strength of 21 , 16 kg / cm². Regressionequation obtained Y = - 0.119 X² + 0.008 X + 35.53 with a correlation value of R² =0.987, meaning that with the addition of plastic has a very strong influence oncompressive strength. So that it can be obtained an illustration that by addingplastic to the manufacture of hollow concrete brick (brick) can affect thecompressive strength decreases. Despite the decline, the quality of the brick is stillgood and above the lowest quality Level IV with compressive strength above 2.0MPa which may still be made with variations Plastic with a composition greaterthan 1% or comparative composition of Portland Cement (PC) with sand is mademore small (<1 PC: 7 Sand), with the hope that this Plastic waste can be utilizedoptimally.Kata kunci : plastic waste, brick making, waste utilization